Does perceived usefulness and perceived ease of use affect intention to use crowdfunding platforms? - Md Husin, Maizaitulaidawati; Haron, Razali; Aziz, Shabab (2019)
This paper aims to address the influence of perceived usefulness (PU) and perceived ease of use (PEOU) on the intention (INT) to use crowdfunding platforms among small-to-medium enterprises (SMEs). Data were collected from 163 SMEs in Selangor, Malaysia, using a purposive sampling approach. The hypotheses were tested by applying structural equation modelling. The results revealed that perceived usefulness and perceived ease of use were able to influence intentions to use crowdfunding platforms. By examining perceived usefulness and perceived ease of use on intention, this paper validated the importance of both constructs in affecting the intention of SMEs in using crowdfunding. The result of this paper will help in guiding efforts of crowdfunding platform providers to formulate strategies that will enhance SMEs intention to use their platforms.